2012
DOI: 10.1029/2011gl050018
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐payload measurement of transverse velocity shears in the topside ionosphere

Abstract: [1] Using a multi-payload sounding rocket mission, we present the first direct measurement of velocity shear in the topside auroral ionosphere. In regions of large, $200 mV/m, transient electric fields we directly measure differences in the plasma drift velocity. From these differences, shear frequencies reaching AE6Hz are measured. These directly measured shears are compared with the shear inferred from single payload measurements. It is shown this traditional measurement of shear overestimates the shear freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The 12 min 43 s flight reached an apogee of 564 km over the northern coast of Alaska at 11:11:11 UT, and left the auroral oval at 11:14:40 UT before atmospheric reentry at 11:16:42 UT. The experiment array design was chosen to address questions about (1) shears in ionospheric electric fields and their ability to drive waves [ Lundberg et al , 2012a, 2012b]; (2) proper motion of auroral structures with respect to the ambient ionosphere (this paper); and (3) quantifying parameters of dispersive Alfvén wave phenomena and their effects on auroral flux tubes.…”
Section: Methods and Instrumentation: The Cascades2 Sounding Rocket Mmentioning
confidence: 99%
“…The 12 min 43 s flight reached an apogee of 564 km over the northern coast of Alaska at 11:11:11 UT, and left the auroral oval at 11:14:40 UT before atmospheric reentry at 11:16:42 UT. The experiment array design was chosen to address questions about (1) shears in ionospheric electric fields and their ability to drive waves [ Lundberg et al , 2012a, 2012b]; (2) proper motion of auroral structures with respect to the ambient ionosphere (this paper); and (3) quantifying parameters of dispersive Alfvén wave phenomena and their effects on auroral flux tubes.…”
Section: Methods and Instrumentation: The Cascades2 Sounding Rocket Mmentioning
confidence: 99%
“…The subpayload carried a thermal electron retarding potential analyzer (ERPA) [ Frederick‐Frost et al , ], a Cornell University GPS Autonomous Receiver (COUGAR) [ Powell et al , ], and the Cornell Wire Boom Yo‐yo (COWBOY) electric field instrument [ Lundberg et al , , ]. As described by Lundberg et al [], the COWBOY instrument consists of a pair of crossed 12.14 m dipole antennas. Potential difference is measured between the 4.45 cm spheres at the end of each coaxial wire boom, as well as between each sphere and the payload skin.…”
Section: Observationsmentioning
confidence: 99%
“…ERPA data (Frederick‐Frost et al, ) from RENU2 are shown in Figure c and illustrate a clear correlation between elevated electron temperatures and the softer particle precipitation. DC electric field measurements from the COWBOY instrument (Lundberg, Kintner, Powell et al, ; Lundberg, Kintner, Lynch et al, , and references therein), Figure d, are small but show an enhancement just equatorward of the cusp/PMAF. These measurements, when compared to the speed of this PMAF, suggest that the PMAF was not locked into the slower background convection; a somewhat unusual situation (e.g., Kozlovsky & Kangas, ).…”
Section: Data Motivating Modeling Effortsmentioning
confidence: 99%